Reestablishment of the Smile after Hypoglossal–Facial Nerve Transfer: What Can We Learn? - Kleijwegt, M.C.; Wever, C.; Hensen, E.F.; Jansen, J.C.; Koot, R.W.; Malessy, M.J.A. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objective The aim of this study was to assess the ability to smile following a hypoglossal–facial nerve transfer (N12–N7).Design This is a retrospective chart review.Setting National tertiary referral center for skull base pathology.Participants Seventeen patients.Main Outcome Measures The ability to smile following an N12–N7 transfer was assessed by five medical doctors on photographs of the whole face and frontal, orbital, and oral segments. The (segmented) photographs were scored for the symmetry, asymmetry, and correct or incorrect assessment of the affected side.Results Seventeen patients were analyzed by 5 assessors providing 85 assessments. The whole face at rest was judged symmetrical in 26% of the cases and mildly asymmetrical in 56%. Frontal, orbital, and oral segments were symmetrical in 63, 20, and 35%, respectively. The affected side was correctly identified in 76%. When smiling, the whole face was symmetrical in 6% and mildly asymmetric in 59%. The affected side was correctly identified in 94%. The frontal, orbital, and oral segments during smiling were symmetrical in 67, 15, and 6%, respectively. The affected side of the frontal, orbital, and buccal facial segments during smiling was correctly identified in 89, 89, and 96%, respectively. Interobserver variability with Fleiss' kappa analysis showed that the strength of the agreement during smile of the total face was good (0.771)Conclusion Following an N12–N7 transfer, a good facial symmetry at rest can be achieved. During smiling, almost all patients showed asymmetry of the face, which was predominantly determined by the orbital and oral segments. To improve the ability to smile after an N12–N7 transfer, additional procedures are needed.
Keywords: vestibular schwannoma; facial reconstruction; hypoglossal; nerve transfers; facial schwannoma